2015
DOI: 10.1016/j.jpainsymman.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Professionals' Inner Life: Exploring the Relationships Among Awareness, Self-Care, and Compassion Satisfaction and Fatigue, Burnout, and Coping With Death

Abstract: The awareness-based model of self-care was successfully tested in a multidisciplinary sample of Spanish palliative care professionals. This research applies a quantitative evaluation of the model, providing evidence of a constellation of key variables for health professionals' quality of life, such as specific training, self-care, awareness and coping with death competency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
235
1
39

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(306 citation statements)
references
References 50 publications
27
235
1
39
Order By: Relevance
“…This could be because they also had opportunities for introspection and to reflect on their own perspective on life and mortality, thereby enhancing their personal growth, self-actualization, and capacity for compassion and life meaning, while at the same time reducing their fear of death (Pessin et al, 2015). These constructs could be a moderator of the psychopathological differences among healthcare practitioners with and without burnout (Chan et al, 2015;Sansó et al, 2015;Slocum-Gori et al, 2011). Other aspects of the inner life of professionals-such as the compassion fatigue/satisfaction continuumhave also been related to palliative care professionals and burnout syndrome (Sansó et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This could be because they also had opportunities for introspection and to reflect on their own perspective on life and mortality, thereby enhancing their personal growth, self-actualization, and capacity for compassion and life meaning, while at the same time reducing their fear of death (Pessin et al, 2015). These constructs could be a moderator of the psychopathological differences among healthcare practitioners with and without burnout (Chan et al, 2015;Sansó et al, 2015;Slocum-Gori et al, 2011). Other aspects of the inner life of professionals-such as the compassion fatigue/satisfaction continuumhave also been related to palliative care professionals and burnout syndrome (Sansó et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing home staff in one study reported their grief to be “disenfranchised” as their relationship with the dying person was unacknowledged, and staff sought to remain professionally detached rather than recognising the impact of death on them (Wilson and Kirshbaum, ). Conversely, working with patients nearing the end of life is also associated with high levels of job satisfaction (Sanso et al ., ) and low levels of distress (Pitfield et al ., ). Other researchers claim that a certain level of stress in end of life care is required in order to function well (Sabo, ).…”
Section: Discussionmentioning
confidence: 99%
“…A dose-dependent response has been suggested (Berger, Polivka, Smoot, & Owens, 2015;Branch & Klinkenberg, 2015;Jakimowicz & Perry, 2015) with support from management a key predictor (Hunsaker, Chen, Maughan, & Heaston, 2015). Self-care and awareness may buffer feelings of compassion fatigue (Sans o et al, 2015).…”
mentioning
confidence: 99%